The values in university teaching. Systematized revision - Briceño Caballero, Maritza Minelli (2024)
Values ​​in teaching are a topic of interest due to their relevance and significance in the training of students. This work aims to compile research that addresses this topic in order to systematize and analyze the body of evidence generated. The review included 32 articles from the SCOPUS, ERIC and Dialnet databases. It was found that the analyzed research shows coincidences in the methodology, data collection technique and results. Furthermore, the importance of values ​​in teaching practice is highlighted and the most mentioned values ​​are responsibility, respect and commitment. Other aspects were also found such as the strategies used in the classroom, some difficulties in teaching values ​​and other variables that may intervene in this process. Based on the results, it is recommended to carry out research that studies and tries to understand the topic in a deeper way using various more complex collection techniques that allow triangulation of information and determine the impact that values ​​have on training and learning. of data students as well as implementing strategies in institutions such as systematic teacher evaluation, the creation of codes of ethics, teacher training and the inclusion of these topics in the study plans.